(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Stylistic devices play the greatest role in the analysis of any kind of literary text. The term “figure of speech” is frequently used for stylistic devices that make use of a figurative meaning of the language elements and thus create a vivid image. Among other figures of speech, repetition is one of the widely used syntactic stylistic devices. The aim of the given article is to discuss the problem of repetition, to give outline of this very important and frequently used stylistic device, its peculiarities and identify those new classes which were revealed after thoroughly studying the material under investigation. Particularly these classes are the novelty that is suggested in the given article.